INTERFAITH MARRIAGE. A DICHOTOMOUS PERSPECTIVE ON NORMATIVE AND LEGAL PRACTICAL DIMENSIONS - Hanapi, Agustin; Husnul, Muhammad; Yuhermansyah, Edi (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
The legal perspective on interfaith marriage in Indonesia, particularly between Muslims and adherents of other religions, is predominantly influenced by Islamic legal norms. The legal regulations have been established in Articles 40 and 44 of the Compilation of Islamic Law. Fundamentally, these regulations prohibit marriage between Muslims and non-Muslim religious adherents. However, the legal construction in Indonesia tends to be non-binding, as opportunities for interfaith marriage practices persist. The Marriage Law Number 1 of 1974, which serves as the foundational legal framework for marriage in Indonesia, has not explicitly prescribed either permission or prohibition. This is substantiated by the prevalence of marriage practices between Muslim men or women and individuals from other religious backgrounds. The dichotomy between legal practices and legal norms consequently leads to a lack of legal certainty regarding its regulation in Indonesia. Therefore, this manuscript comprehensively elucidates interfaith marriage from Islamic legal perspectives, positive legal frameworks, and its practical legal implementation within the Indonesian context.